A cobertura das ações policiais na televisão: uma análise de relações de poder no programa Brasil Urgente - Barata, João Medeiros (2011)
This dissertation aims to identify and analyze power relations passing through the coverage of police actions in the Brazilian television, more specifically on the Brasil Urgente program, aired by Bandeirantes TV Station since 2001. In order to do that, the theoretical contributions of Michel Foucault regarding the construction of abnormals, security practices, and dispositifs, as well as those by Gilles Deleuze and Félix Guattari related to the agencements and the societies of control were used. For doing this, thirty editions aired between 05/10/2010 and 07/01/2010 were collected and their reports were analyzed in order to portray how this program promotes meetings with power, how abnormals are created, which practices of security are disseminated through this discourse, and, finally, how this kind of coverage presents practices from the societies of discipline and control